Report of the Conference Miasto po obu brzegach rzeki - różne oblicza kultury [A City on Both Banks of a River - Various Aspects of Culture]. October 18-20, 2007, Warsaw, Poland.: Organizers: Polskie Towarszystwo Etnologii Miasta, Muzeum Historyczne m. st. Warszawy, Muzeum Niepodległości, Archiwum Państwowe m. st. Warszawy, Czeskie Centrum, Instytut Słowacki - Novotná, Hedvika (Lidé města, 2007)
Polish ethnology, in particular cultural and social anthropology, has been dedicated for a long time to urban topics. This interest is expressed in the anchoring of urban studies in the Polish Society of Urban Ethnology (Polskie Towarzystwo Etnologii Miasta) which came into being in the year 2000. The subject of interest of this society is the problematics of the social-cultural identity of cities with a view to changes which, at least since the 19th century, accompany the growth of cities and with them the adjoining regions. One of the most importantactivities of the Polish Society of Urban Ethnology is the organization of international thematically oriented conferences – e.g., Sfera sacrum i profanum w kulturze współczesnych miast europy środkowej (The sacred and profane sphere in the culture of contemporary Central European cities (Warsaw – Pultusk, Sept. 16-18, 2004), ); Miejsca biesiadne. Co o nich opowiada antropolog? (Places for parties; what does an anthropologist have to say about them?) (Lodz, June 1–2, 2006).